Beginning CakePHP From Novice to Professional - Golding, David; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2008)
CakePHP is a leading PHP–based web app development framework. When asking a question on forums or chat rooms, many CakePHP beginners get little help from the experts. Simple questions can get a response like, “Well, just read the online manual and API.” Unfortunately, the online manual is depreciated, and who wants to absorb a programming language or framework from an API? Beginning CakePHP will do the following: Lead you from a basic setup of CakePHP to building a couple applications that will highlight CakePHP’s functionality and capabilities without delving too deeply into the PHP language, but rather what the CakePHP framework can offer the developer. Teach you to use CakePHP by incorporating advanced features into your web development projects. Target beginners of CakePHP or web frameworks in general as well as experienced developers with limited exposure to CakePHP. A secondary audience may include developers undecided on adopting CakePHP or business managers trying to assess the value of incorporating CakePHP into their toolbox.
Getting Started -- Installing and Running CakePHP -- Creating a To-Do List Application -- Developing CakePHP Applications -- Naming Files and Designing the Database -- Creating Simple Views and Baking in the Console -- Customizing Views -- Working with Controllers and Models -- Implementing Ajax Features -- Advanced CakePHP -- Helpers -- Routes -- Components and Utilities -- Vendors -- Plugins -- DataSources and Behaviors -- Wrapping Up the Application.
Keywords: Computer programming; Software engineering; Web Development; Software Engineering/Programming and Operating Systems